Informática na educação: o uso da linguagem computacional LOGO no estudo das operações cognitivas da fase lógico-formal, tal como descritas por Piaget - Bernadete Tassara Lemos Braulio (1989)
The objetive of this dissertation is to analyse the use of LOGO in the study of the cognitive operations of the formal-logical stage as described by Piaget. In order to achieve this objective, a research was conducted with six individuals, 12 yar and 9 month to 14 year-old, students of the Pedagogic Center of the Federal University of Minas Gerais.Those individuals, who had previously go to.Know the main conmands of GRAPHIC-LOGO, used them to solve six challenges related to the cognitive operations of compensation, proportion, combination, permutation and probability.Data collection and analysis were based on the clinical method.The main conclusions point out the efficacy of LOGO language in identifying cognitive operations and in hlping their development as well as the analysis of the various strategies used by the students.However, research results showed that LOGO efficacy is a function of the individual himself and of the task nature.This way, the use of LOGO was more efficacious for those who had not presented complete domain of the cognitive operations studied and also in simulating situations difficult to be presented to the students. The use of LOGO lanuage and its related educationl research are suggested not only in the case of spontaneous situations, as usually observed in the papers, but also in situations involving curriculum subject systematic learning.